PENGARUH DESAIN PRODUK DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN PADA MARKET PLACE SHOPEE - Febrianti, Nur Lia; Islamuddin, Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to determine the effect of product design on purchasing decisions for Ventela brand shoe customers in Bengkulu City. To determine the effect of Online Customer Rating on Purchasing Decisions for Ventela brand shoe customers in Bengkulu City. To find out the influence between Product Design and Online Customer Rating on Purchasing Decisions for Ventela brand shoe customers in Bengkulu City. This type of research is research using a quantitative approach. "Quantitative methods are used to examine specific populations and samples. Based on the results of research on the effect of Product Design and Online Customer Rating simultaneously on Purchasing Decisions for Ventela Brand shoe customers in Bengkulu City, the following conclusions can be made:  There is a positive and significant effect of Product Design (X1) on Purchasing Decisions (Y) at Market Place Shopee on Ventela brand shoe customers in Bengkulu City, which means that the higher the Product Design, the more the Purchasing Decision increases. There is an influence of Customer Online Rating (X2) on Purchasing Decisions (Y) in the Shopee market place for Ventela brand shoe customers in Bengkulu City. This means that the higher the Online Customer Rating, the more the Purchasing Decision increases. There is an effect of Product Design and Online Customer Rating together on Purchasing Decisions at the Shopee market place for Ventela brand shoe customers in Bengkulu City with an Fsiq value of 0.000 <0.05. Keywords: Product Design, Online Customer Rating, Purchase Decision